Analisis keterampilan menulis tegak bersambung pada peserta didik kelas II sekolah dasar - Ursida, Vellina Glinca; Rintayati, Peduk; Adi, Fadhil Purnama (Didaktika Dwija Indria, 2022)
The purpose of this research is to analyze the cursive writing skills of second grade students. This research applies qualitative method of research and a case analysis methodological approach. The subjects of this research is a teacher and 14 students. The cursive writing skills of second grade students at SDN Tunggulsari 1 Surakarta are the topic of this research. In this research, cursive writing skills were evaluated using eight indicators: form, letter size, distance, slope, alignment, neatness, completion of letters, use of capital letters, and use of punctuation marks. The primary data of this research obtained through interviews with homeroom teacher, second grade students and obtained by observation. The secondary data used by researcher was the study of documents and documentation. The techniques in collecting data were observation, interviews, and the study of documents. The researcher applied source triangulation to validate the data. The Miles and Huberman model analytic procedures were used in this research. The results revealed that the cursive writing skills of second grade students remained deficient. The results of the research of cursive writing abilities based on eight indicators revealed that only five students are classified as sufficient, while the remaining nine students are classified as deficient.Kata kunci: second grade students, elementary school, cursive, cursive writing skill.